Janus kinase inhibitors ruxolitinib and baricitinib impair glycoprotein-VI mediated platelet function. (3rd April 2022) - Parra-Izquierdo, Iván; Melrose, Alexander R.; Pang, Jiaqing; Lakshmanan, Hari Hara Sudhan; Reitsma, Stéphanie E.; Vavilapalli, Sai Hitesh; Larson, Mark K.; Shatzel, Joseph J.; McCarty, Owen J. T.; Aslan, Joseph E.
Abstract: Several Janus kinase (JAK) inhibitors (jakinibs) have recently been approved to treat inflammatory, autoimmune and hematological conditions. Despite emerging roles for JAKs and downstream signal transducer and activator of transcription (STAT) proteins in platelets, it remains unknown whether jakinibs affect platelet function. Here, we profile platelet biochemical and physiological responses in vitro in the presence of five different clinically relevant jakinibs, including ruxolitinib, upadacitinib, oclacitinib, baricitinib and tofacitinib. Flow cytometry, microscopy and other assays found that potent JAK1/2 inhibitors baricitinib and ruxolitinib reduced platelet adhesion to collagen, as well as platelet aggregation, secretion and integrin αIIb β3 activation in response to the glycoprotein VI (GPVI) agonist collagen-related peptide (CRP-XL). Western blot analysis demonstrated that jakinibs reduced Akt phosphorylation and activation following GPVI activation, where ruxolitinib and baricitinib prevented DAPP1 phosphorylation. In contrast, jakinibs had no effects on platelet responses to thrombin. Inhibitors of GPVI and JAK signaling also abrogated platelet STAT5 phosphorylation following CRP-XL stimulation. Additional pharmacologic experiments supported roles for STAT5 in platelet secretion, integrin activation and cytoskeletal responses. Together, our results demonstrate that ruxolitinib and baricitinib have inhibitory effects on platelet function in vitro and support roles for JAK/STAT5 pathways in GPVI/ITAM mediated platelet function.